2019
DOI: 10.1021/acs.jpcc.9b04309
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Spinel MnCo2S4 on Carbon Nanotubes as Efficient Counter Electrodes for Quantum Dot Sensitized Solar Cells

Abstract: Ternary spinel MnCo2S4 was anchored on carbon nanotubes (CNTs) via a two-step method of precursor preparation followed by ion exchange, and employed as efficient counter electrodes for quantum dot sensitized solar cells (QDSSCs). Electrochemical tests show that the interface charge transfer resistance (R ct) of MnCo2S4 is only 2.86 Ω and the R ct of MnCo2S4/CNTs further decrease to 1.09 Ω, suggesting both MnCo2S4 and its composite exhibit excellent catalytic activity for S n 2– reduction. The power conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Hence wrapping the metal sulfide with the carbon materials has a better outlook for increasing the electrocatalytic activity and PCE . Apart from MWCNTs, GQDs possess unique advantages, i.e., high electron extraction, quantum confinement effect, and a multi-exciton effect. , To compare the electrode encapsulated with MWCNTs and GQDs, the researcher found that a ternary metal sulfide with MWCNTs/GQDs shows the best result due to the large surface area and abundant active sites. Furthermore, the samples were employed as a working electrode, and the effect on the supercapacitor performance was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hence wrapping the metal sulfide with the carbon materials has a better outlook for increasing the electrocatalytic activity and PCE . Apart from MWCNTs, GQDs possess unique advantages, i.e., high electron extraction, quantum confinement effect, and a multi-exciton effect. , To compare the electrode encapsulated with MWCNTs and GQDs, the researcher found that a ternary metal sulfide with MWCNTs/GQDs shows the best result due to the large surface area and abundant active sites. Furthermore, the samples were employed as a working electrode, and the effect on the supercapacitor performance was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The sharp peak at 613 could corresponds to the lattice vibration of MnÀ O and MnÀ S. The small shoulder observed in the range of 430-455 cm À 1 along with the sharp peak at 485 cm À 1 is related to the CoÀ S bonding vibrations. [40] The peak observed at 312 and 350 cm À 1 is related to the MnÀ O bond. [41] The sharp peak observed at 190 cm À 1 corresponds to the stretching mode of CoÀ O bonds.…”
Section: Resultsmentioning
confidence: 97%
“…It can be seen that an additional satellite peak located at 169.0 eV, which is due to the high surface oxidation state of sulfur, such as sulfate(SO 4 2À ). [20] The peaks described above are the typical metal sulfur bond in the ternary metal sulphide. In conclusion, the above results confirm that the chemical composition contained Mn 3 + , Mn 2 + , Co 3 + , Co 2 + and S 2À in the near-surface of MnCo 2 S 4 /CC.…”
Section: Resultsmentioning
confidence: 99%
“…What's more, TMSs can be expediently obtained by sulfurization of transition metal oxides/hydroxides with designed structure and morphology. Among them, MnCo 2 S 4 shows outstanding electrochemical performance in high‐performance supercapacitors, [17] electrochemical water splitting, [18] sodium‐ion battery [19] and other electrochemical fields [20] . Zhang et al.…”
Section: Introductionmentioning
confidence: 99%